Vulnerability in Research: Basic Ethical Concepts and General Approach to Review - Gordon, Bruce G. (The Ochsner journal, 2020)
The concept of vulnerability is a cornerstone of the theoretical basis and practical application of ethics in human subjects research. Risks to humans participating in research must be minimized; that is, subjects must be offered protection from risks. Vulnerable subjects require additional protections. This paper reviews the ethical and conceptual basis of vulnerability within the context of human subjects research and suggests a basic approach that institutional review boards (IRBs) can use when considering if the research includes adequate safeguards to protect the rights and welfare of subjects who are likely to be vulnerable. Two distinct approaches to describing the features that make a person vulnerable are the categorical approach and the contextual approach. The categorical approach considers certain groups or populations as vulnerable. This approach is not optimal because it does not address persons with multiple vulnerabilities, does not account for variation in the degree of vulnerability within the group based on individual characteristics, and classifies certain persons as vulnerable rather than identifying situations in which individuals might be considered vulnerable. The alternate contextual approach allows for a more nuanced understanding of the nature of the vulnerability than the categorical approach and therefore a more focused approach to safeguards. The IRB is charged with ensuring that additional safeguards to protect the rights and welfare of subjects who are likely to be vulnerable are included in the study under review. To make this determination, the IRB might be advised to consider two questions: (1) is inclusion necessary? and (2) if so, are safeguards adequate? Although vulnerability is often presented as a yes/no consequence related to some characteristic of a group, a more accurate approach is to consider vulnerability as occurring along a spectrum of seriousness and as a consequence of situations and context. With this idea in mind, investigators and IRBs are advised to take a stepwise approach to determining if the study meets the regulatory and ethical admonition to ensure that safeguards protect the rights and welfare of vulnerable subjects.